Mexican Americans in San Antonio Texas: An analysis of their insertion in formal self-employment - José Luis Manzanares Rivera (Estudios Fronterizos, 2015)
This paper analyzes the insertion of the Mexican population in the job market in San Antonio, Texas. In particular, it responds to the question of what determines employment in individual, formally incorporated businesses. The methodology analyzes microdata from the American Community Survey (acs) using a logistic statistical estimation tool. The main results indicate that attributes such as command of the English language or an individual’s origin could contribute to an understanding of job market insertion for the Mexican population living in the U.S. and do not necessarily constitute barriers for labor market insertion in the self-employment category in cities with traditional migration such as San Antonio, Texas.